2007
DOI: 10.1515/pteridines.2007.18.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Reference Standard of Serum Neopterin Concentration in Healthy Children

Abstract: Introduction: Increased neopterin concentrations are observed in many diseases in which cell immunity is stimulated. A quick and sensitive method for monitoring the changes in immune system can be useful for understanding etiopathogenesis of the disease and choosing the appropriate treatment. There are only few known data concerning normal serum neopterin value in children, therefore the wide clinical use of this parameter is limited. Aim: to evaluate the referential neopterin concentration in serum in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, the age effect on Neo levels may be more visible when comparing between age classes (e.g., children to adults) rather than within. Plata-Nazar et al (2007) and Satoh et al (1998) also found no age dependence when examining Neo levels within children and adolescents. In our study individuals, uNeo levels showed a high degree of intra-individual fluctuation which is found in children as well while levels in adults are stable (Winkler et al 2003).…”
Section: Relation Of Disease Markers and Potential Use Of Uneomentioning
confidence: 88%
“…However, the age effect on Neo levels may be more visible when comparing between age classes (e.g., children to adults) rather than within. Plata-Nazar et al (2007) and Satoh et al (1998) also found no age dependence when examining Neo levels within children and adolescents. In our study individuals, uNeo levels showed a high degree of intra-individual fluctuation which is found in children as well while levels in adults are stable (Winkler et al 2003).…”
Section: Relation Of Disease Markers and Potential Use Of Uneomentioning
confidence: 88%
“…The determined neopterin concentrations in blood serum of children from this group were used to establish reference values. The cut-off point of serum neopterin concentration, irrespective of children's age or sex, was 11 nmol/l (Plata-Nazar et al, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…Pteridines can occur in three oxidation states with different stability 51 . Many authors mentioned different sensitivity in fluorescence detection of pteridines arising from their oxidation properties, among others also from the sensitivity to light 52,53 . At neutral pH, reduced forms are easily oxidized by molecular oxygen giving rise to stable fluorescent forms.…”
Section: Optimization Of Extraction Storage and Lc-ms/ms Methods Onmentioning
confidence: 99%